2009
DOI: 10.1073/pnas.0902768106
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic, nondeterministic circadian rhythm generation in identified mammalian neurons

Abstract: Circadian rhythms are modeled as reliable and self-sustained oscillations generated by single cells. The mammalian suprachiasmatic nucleus (SCN) keeps near 24-h time in vivo and in vitro, but the identity of the individual cellular pacemakers is unknown. We tested the hypothesis that circadian cycling is intrinsic to a unique class of SCN neurons by measuring firing rate or Period2 gene expression in single neurons. We found that fully isolated SCN neurons can sustain circadian cycling for at least 1 week. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
220
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(249 citation statements)
references
References 47 publications
21
220
4
Order By: Relevance
“…Approximately 40% of cells in each SCN explant lost observable rhythmicity during TTX application, corresponding with ref. 36. These cells were not included in this figure, although they were included in the bioluminescence traces from the post-TTX resynchronization period used to infer network connectivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 40% of cells in each SCN explant lost observable rhythmicity during TTX application, corresponding with ref. 36. These cells were not included in this figure, although they were included in the bioluminescence traces from the post-TTX resynchronization period used to infer network connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…1A for SCN1. TTX was applied to the whole tissue explants for 6 d to inhibit intercellular coupling while leaving physical connections within the tissue intact (28,36,37). After 6 d, the TTX was washed out, and recordings continued for an additional 8 d as neurons in the network regained synchrony.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, more research needs to be done to define the nature of this food-entrained network. Recently it has been shown that the oscillatory property of the SCN is possibly a network property rather than the property of single neurons (43). We may therefore need to view in a similar manner the FEO as a neuronal network: its oscillatory capacity is neither derived nor dependent (as we have shown here) on one structure, but rather the interaction between the participating structures shapes, different aspects of FAA.…”
Section: Faa Is Lost After Lesion Of the Dmh But Reappears After Amentioning
confidence: 94%
“…Isolated SCN neurons are less reliable oscillators (11) and "neuronal network properties are integral to normal function of the SCN" (ref. 9, p. 551).…”
mentioning
confidence: 99%